Targeting the IL-15/CD122 signaling pathway: reversing TRM cell-mediated immune memory in vitiligo - Su, Xiangxi; Liu, Fang (Frontiers in Immunology, 2025)
Vitiligo is a chronic autoimmune disorder in which melanocyte−specific CD8+ T cells destroy pigment−forming cells, producing persistent depigmented macules. Recurrence after treatment implicates tissue−resident memory T (TRM) cells that are maintained by interleukin−15 (IL−15) signaling. Here we review current insights into TRM−cell biology, summarize experimental and emerging clinical data targeting the IL−15/CD122 axis—including the ongoing Phase 2a AMG 714 trial—and discuss combination strategies with approved topical Janus kinase inhibitors such as ruxolitinib cream. Disrupting IL−15 may offer durable repigmentation with minimal systemic immunosuppression.